Предмет: Алгебра,
автор: Нима208
упростить выражение плиз а)(4а^2+9а)-(а^2-1+9а) б)6а^4-2а^2(3а^2+а) в)4у^3-(1+2у)(2у^2-у) г)(х+3)^2-(х-2)(х+2)
Ответы
Автор ответа:
0
а)(4а²+9а)-(а²-1+9а)=4а²+9а-а²+1-9а=3а²+1
б)6а^4-2а²(3а²+а)=6а^4-6а^4-2а³=-2а³
в)4у³-(1+2у)(2у²-у)=4у³-2у²+у-4у³+2у²=у
г)(х+3)²-(х-2)(х+2)=х²+6х+9-(х²-4)=х²+6х+9-х²+4=6х+13
б)6а^4-2а²(3а²+а)=6а^4-6а^4-2а³=-2а³
в)4у³-(1+2у)(2у²-у)=4у³-2у²+у-4у³+2у²=у
г)(х+3)²-(х-2)(х+2)=х²+6х+9-(х²-4)=х²+6х+9-х²+4=6х+13
Автор ответа:
0
спасибо
Автор ответа:
0
не за что)
Похожие вопросы
Предмет: Математика,
автор: ailnicka2008
Предмет: Математика,
автор: Slavil
Предмет: Математика,
автор: dpencik737
Предмет: Математика,
автор: autovlg
Предмет: Математика,
автор: Kary345